2018
DOI: 10.1021/acs.cgd.7b01170
|View full text |Cite
|
Sign up to set email alerts
|

Additive Induced Formation of Ultrathin Sodium Chloride Needle Crystals

Abstract: A multitude of ultrathin crystal needles are formed during the evaporation of saturated aqueous NaCl solution droplets in the presence of amide containing additives. The needles are as small as 300 nm wide and 100–1000 μm in length. Heating experiments, X-ray diffraction, and energy dispersive X-ray spectroscopy showed that the needles are cubic sodium chloride crystals with the needle length direction pointing toward [100]. This shape, not expected for the 43̅m point group symmetry of NaCl, has been explained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 24 publications
1
23
1
Order By: Relevance
“…The formation of these acicular particles may be closely related to the drastic increase in crystallite size in the 012 direction. Moreover, GLDA inhibited the caking of aragonite particles, which may imply a lower surface energy of aragonite 28 , 47 . In the presence of GLDA, Ca ions were gradually released from Ca-GLDA complexes for carbonation, and the resulting low Ca 2+ /CO 3 2− ratio was considered to induce aragonite formation 29 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of these acicular particles may be closely related to the drastic increase in crystallite size in the 012 direction. Moreover, GLDA inhibited the caking of aragonite particles, which may imply a lower surface energy of aragonite 28 , 47 . In the presence of GLDA, Ca ions were gradually released from Ca-GLDA complexes for carbonation, and the resulting low Ca 2+ /CO 3 2− ratio was considered to induce aragonite formation 29 .…”
Section: Resultsmentioning
confidence: 99%
“…However, different chelating agents may have different effects on interfacial energy. Westin and Rasmuson (2005) reported that the inclusion of chelating agents such as EDTA notably increased the interfacial energy 26 , whereas Townsend et al (2018) reported that nitrilotriacetamide (NTAA), methylglycine diacetamide (MGDA), and N,N -dicarboxymethyl glutamic acid (GLDA) decreased the interfacial energy and thus promoted the precipitation of acicular NaCl crystals 28 . On the other hand, the complexation of Ca ions by chelating agents results in a gradual release of these ions during carbonation and, hence, in a low Ca 2+ /CO 3 2− ratio.…”
Section: Introductionmentioning
confidence: 99%
“…[27] Notably, in this case, the growth mode of the NaBH 4 bars may occur along the [100] direction as previously observed in the case of cubic NaCl crystals elongated as needles. [28] The crystal structure of NaBH 4 is isomorphous to NaCl; therefore, the nucleation and growth of NaBH 4 can also be explained based on the studies on NaCl crystals. [28,29] Wang et al [29d] argued that the formation of cubic morphology of NaCl is due to the fast diffusivity of Na þ and Cl À ions and a nondirectional growth in aqueous solutions.…”
Section: Synthesis Of Varied Nabh 4 Morphologiesmentioning
confidence: 99%
“…In aqueous solution, the growth shape of a NaCl crystal is generally rectangular and the direction of the growth of dendrites is generally 〈110〉 or 〈111〉 (Goto et al, 2016). It is commonly observed that the growth shape of NaCl crystals is dependent on the solvent (Stoica et al, 2004) and that the shape of NaCl crystals can be changed by the presence of an organic additive in an aqueous solution of NaCl (Townsend et al, 2018). In our experiments, the dendritic shape of the NaCl crystal was caused by the acetone, possibly due to differences in solvent-surface interactions from those in aqueous solution inducing drastic changes in facial growth rates (Stoica et al, 2004).…”
Section: Crystal Shapementioning
confidence: 99%